Travelling choices made easier using dijkstra algorithm / Wardah Mohd Nor and Noraini Noordin - Mohd Nor, Wardah; Noordin, Noraini
Current inflating high cost of living may affect mobility of students to commute between their university and any other destination. In an attempt to help solve or minimise the problem, several proposed travel alternative modes from this research may help students to identify the shortest path and minimum cost path in a journey. In finding the minimum total travel cost and shortest total completion time for a journey between two destinations, the step-by-step Dijkstra algorithm was applied in the time-dependent shortest path problem (TDSPP) and cost-dependent shortest path problem (CDSPP) in this research. Interestingly, both problems treated separately mapped out two different paths with two different costs. The former mapped out a route from UiTM Perlis Branch to Arau by taxi, train from Arau to Alor Setar, and Malaysia Airlines flights from Alor Setar to Kuala Lumpur and on to Johor Bahru. The other route was best described by taxi from Arau to Alor Setar, Air Asia flight from Alor Setar to Kuala Lumpur and train from Kuala Lumpur to Johor Bahru.